Assessing the Safety Behaviour of the Bus Express Driving Condition from the Passengers' Perspective - Abdullah, Shahrum; Karam Singh, Salvinder Singh; Azman, Abdul Hadi; Mat Yazid, Muhamad Razuhanafi; Hishamuddin, Hawa; Wan Ghopa, Wan Aizon; Shahrir, Aini Hazwani; Mohd Ihsan, Ahmad Kamal Ariffin; Abd. Wahab, Dzuraidah (International Journal of Integrated Engineering, 2020)
This paper presents the passengers' perspective towards express bus safety issues based on the driver's behavioural characteristics, providing an important aspect in reducing the accidents in Malaysia.  A pilot study with a respondent of 40 people, aged between 16 to 41 years old were conducted in Universiti Kebangsaan Malaysia. The developed questionnaires based on the five-point Likert Scale were implemented to assess the safety perception on express buses, and it has a higher reliability of Cronbach's Alpha score at 0.91. The findings show that more than 45 % of the respondents agreed that dangerous behaviour of express bus drivers were mainly due to the use of mobile during driving (63.33%), tailgating (57.58%) and driving above the given speed limit (48.59%). The reason of this behaviour is insufficient time to stick to running schedules and the shift pattern rotations. In terms of safety precautions, about 77% passengers preferred safety briefing using audio due to its ease in understanding the meaningful instruction. In addition, 97% passengers agreed on the needs of a second driver to ensure a safe journey to their destination. Hence, a proposed mitigated solution such as drivers monitoring is needed by the respective agencies to reduce this careless behaviour that may influence the dangerous driving behaviour.